IDENTIFIKASI KAWASAN RAWAN BENCANA LONGSOR METODE SKORING DAERAH MOJOTENGAH DAN SEKITARNYA, KECAMATAN REBAN, KABUPATEN BATANG, PROVINSI JAWA TENGAH - reza_krisnandi reza krisnandi; Obrin Trianda; Al Hussein Flowers Rizqi (Retii, 2021)
Administratively the research area is included in the Dieng Volcano Complex which consists of several volcanoes that have slopes steep. The steep slope is one of the main occurrences of landslide movements. Determination of landslide-prone areas using a scoring method with GIS software with parameters such as slope, rock type, soil type class, rainfall, and land use. Based on these 5 parameters, the research area is divided into 3 low landslide-prone areas with a value of 33.00-52.00 with an area of ​​24.19% of the research area which is generally spread out in the northern part of the research area occupying areas with relatively gentler slopes. Areas prone to moderate landslides with a value of 52.01-61.00 with an area of ​​28.91% of the research area which are generally spread out in the middle of the research area occupy areas with relatively steep slopes. Areas prone to landslides are high with a value of 61.01-80.00 with an area of ​​46.90% of the research area which is generally spread in the uthern part of the researh area occupying areas with steep-very steep slopes. Keywords: Disaster, Vulnerability, Landslide, Mojotengah.